Role of Brain Ang (1-7) With Combination Therapy of Aliskerin in Control of Diabetic Nephropathy - Shakya, Richa; Gupta, Jeetendra Kumar; Mazumder, Avijit (Indian Journal of Pharmaceutical Education and Research, 2025)
Objectives: Angiotensin (1-7) system has been recognizing as physiologically major content of the renin-angiotensin system. It exhibited that Diabetic Nephropathy (DN), which is prevalent causes of end-stage renal disease, reduces Ang (1-7) peripheral activity. RAS activity in the PNS is controlled by RAS in the brain. The goal of this research is to see whether cerebral angiotensin (1-7) has a role in chronic diabetic kidney disease in wistar rats. Methods and Materials: Single dosage of streptozotocin 35 mg/kg i.p causes Diabetes Mellitus (DM). 2 doses of aliskerin and Ang (1-7) via a various route. After that there were testing of the samples. Commercially available kits were used to determine biochemical parameters linked to DN. Results: When streptozotocin was given to diabetic rats for 10 weeks, the mice displayed higher serum creatinine, blood urea as well as protein in urine, as well as a decreased amount of serum nitrite. A 2-week course of intracerebral aliskerin (100 nmol/day) and Ang (1-7) treatment decreased such changes also elevated serum nitrite in rats with DN, but only in conjunction with Ang (1-7) (4.8 g/day) separately or in combinations. Conclusion: The findings of current research imply that brain Ang (1-7) is vital in RAS peripheral activity modulation in diabetic nephropathy, which might be attributed to Ang II peripheral activity and reduced central sympathetic outflow.
Keywords: Angiotensin (1-7); Diabetic nephropathy; End-Stage Renal Disease (ESRD); Aliskerin; Peripheral activity; Renin angiotensin system